# excel 统计函数： 通过使用 RANK 表示扎

### 语法

``RANK(number, ref, order)``

### 用法的示例

 10 =rank(a1,\$a\$1:\$a\$12,1) = b1 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A1,\$A\$1:\$A\$12,0)-RANK(\$A1,\$A\$1:\$A\$12,1)) / 2 =rank(a1,\$a\$1:\$a\$12,0) = e1 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A1,\$A\$1:\$A\$12,0)-RANK(\$A1,\$A\$1:\$A\$12,1)) / 2 21 =rank(a2,\$a\$1:\$a\$12,1) = b2 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A2,\$A\$1:\$A\$12,0)-RANK(\$A2,\$A\$1:\$A\$12,1)) / 2 =rank(a2,\$a\$1:\$a\$12,0) = e2 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A2,\$A\$1:\$A\$12,0)-RANK(\$A2,\$A\$1:\$A\$12,1)) / 2 21 =rank(a3,\$a\$1:\$a\$12,1) = b3 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A3,\$A\$1:\$A\$12,0)-RANK(\$A3,\$A\$1:\$A\$12,1)) / 2 =rank(a3,\$a\$1:\$a\$12,0) = e3 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A3,\$A\$1:\$A\$12,0)-RANK(\$A3,\$A\$1:\$A\$12,1)) / 2 21 =rank(a4,\$a\$1:\$a\$12,1) = b4 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A4,\$A\$1:\$A\$12,0)-RANK(\$A4,\$A\$1:\$A\$12,1)) / 2 =rank(a4,\$a\$1:\$a\$12,0) = e4 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A4,\$A\$1:\$A\$12,0)-RANK(\$A4,\$A\$1:\$A\$12,1)) / 2 21 =rank(a5,\$a\$1:\$a\$12,1) = b5 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A5,\$A\$1:\$A\$12,0)-RANK(\$A5,\$A\$1:\$A\$12,1)) / 2 =rank(a5,\$a\$1:\$a\$12,0) = e5 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A5,\$A\$1:\$A\$12,0)-RANK(\$A5,\$A\$1:\$A\$12,1)) / 2 33 =rank(a6,\$a\$1:\$a\$12,1) = b6 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A6,\$A\$1:\$A\$12,0)-RANK(\$A6,\$A\$1:\$A\$12,1)) / 2 =rank(a6,\$a\$1:\$a\$12,0) = e6 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A6,\$A\$1:\$A\$12,0)-RANK(\$A6,\$A\$1:\$A\$12,1)) / 2 33 =rank(a7,\$a\$1:\$a\$12,1) = b7 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A7,\$A\$1:\$A\$12,0)-RANK(\$A7,\$A\$1:\$A\$12,1)) / 2 =rank(a7,\$a\$1:\$a\$12,0) = e7 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A7,\$A\$1:\$A\$12,0)-RANK(\$A7,\$A\$1:\$A\$12,1)) / 2 52 =rank(a8,\$a\$1:\$a\$12,1) = b8 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A8,\$A\$1:\$A\$12,0)-RANK(\$A8,\$A\$1:\$A\$12,1)) / 2 =rank(a8,\$a\$1:\$a\$12,0) = e8 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A8,\$A\$1:\$A\$12,0)-RANK(\$A8,\$A\$1:\$A\$12,1)) / 2 52 =rank(a9,\$a\$1:\$a\$12,1) = b9 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A9,\$A\$1:\$A\$12,0)-RANK(\$A9,\$A\$1:\$A\$12,1)) / 2 =rank(a9,\$a\$1:\$a\$12,0) = e9 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A9,\$A\$1:\$A\$12,0)-RANK(\$A9,\$A\$1:\$A\$12,1)) / 2 52 =rank(a10,\$a\$1:\$a\$12,1) = b10 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A10,\$A\$1:\$A\$12,0)-RANK(\$A10,\$A\$1:\$A\$12,1)) / 2 =rank(a10,\$a\$1:\$a\$12,0) = e10 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A10,\$A\$1:\$A\$12,0)-RANK(\$A10,\$A\$1:\$A\$12,1)) / 2 61 =rank(a11,\$a\$1:\$a\$12,1) = b11 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A11,\$A\$1:\$A\$12,0)-RANK(\$A11,\$A\$1:\$A\$12,1)) / 2 =rank(a11,\$a\$1:\$a\$12,0) = e11 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A11,\$A\$1:\$A\$12,0)-RANK(\$A11,\$A\$1:\$A\$12,1)) / 2 73 =rank(a12,\$a\$1:\$a\$12,1) = b12 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A12,\$A\$1:\$A\$12,0)-RANK(\$A12,\$A\$1:\$A\$12,1)) / 2 =rank(a12,\$a\$1:\$a\$12,0) = e12 + (COUNT(\$A\$1:\$A\$12) + 1-RANK(\$A12,\$A\$1:\$A\$12,0)-RANK(\$A12,\$A\$1:\$A\$12,1)) / 2

``(COUNT(ref) + 1 – RANK(number, ref, 0) – RANK(number, ref, 1))/2.``

### 结论

#### 警告：本文已自动翻译

Microsoft Office Excel 2007, Microsoft Office Excel 2003

• kbmt kbexpertisebeginner kbinfo KB828678 KbMtzh